Morphological Characteristics POD of 5 Cocoa Clones in Suka Agung Village, Lumbok District, Tanggamus Regency - Fauziah, Lu'lu' Kholidah; Permatasari, Nindy; Sari, Resti Puspa Kartika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tanggamus Regency has a large potential for plantation resources. More than 85% of its land is classified as suitable for cocoa cultivation. Optimizing this potential requires the use of superior cocoa clones with pod morphological characteristics that support high productivity. This study aims to determine the quantitative pod morphological characteristics of 5 cocoa clones and identify the most suitable clones for cultivation in Suka Agung Village, Bulok District, Tanggamus Regency. The research method is a survey with a purposive sampling method. Quantitative pod morphological data were analyzed using ANOVA and DMRT at a significance level of 5%. The results showed that MCC 01 and MCC 02 showed better quantitative characteristics than other clones. This was indicated by higher average pod diameter, number of seeds per pod, seed length, seed diameter, and number of seeds per 100 g. However, the MCC 01 clone is considered to have moderate resistance to Vascular Streak Dieback (VSD) and Cocoa Pod Borer (CPB). In conclusion, MCC 02 is suitable for cocoa cultivation in Suka Agung Village, Lumbok District, Tanggamus.